High-strength toughened CPVC (Chlorinated Polyvinyl Chloride) pipe and preparation method thereof

Modified elastomer and compatible agent were prepared by emulsion polymerization. Combined with nano SiO2 surface modification, the problem of CPVC pipes being easily broken under low temperature environments or when impacted by external forces is solved, and high-strength and toughened CPVC pipes are achieved.

CN119613899AInactive Publication Date: 2025-03-14SHANGHAI BST TUBING

Patent Information

Application Number
CN202510158004.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing CPVC pipelines are prone to cracking or breaking in low temperature environments or when impacted by external forces, which is difficult to meet actual needs.

Method used

Modified elastomer is prepared by emulsion polymerization method, and ethyl methacrylate 2-sulfonate is introduced as a functional monomer to enhance the high polarity and flexibility of the compatibility agent and enhance the interface binding force between the modified elastomer and the CPVC matrix. At the same time, the nano SiO2 is surface modified by a silane coupling agent to enhance the dispersion and interface interaction of the inorganic filler in the matrix.

Benefits of technology

It improves the rigidity, heat resistance and dimensional stability of the material, enhances the impact resistance and crack resistance of CPVC pipes, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613899A_ABST
    Figure CN119613899A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of CPVC pipe preparation, and provides a high-strength toughened CPVC pipe and a preparation method thereof. Firstly, butadiene and divinyl benzene are copolymerized to form a high-crosslinking structure, rigid support is provided, butyl methacrylate and acrylonitrile are copolymerized, flexibility and polarity are adjusted, interface bonding force is enhanced, and acrylic acid, epoxy acrylate and ethyl methacrylate are copolymerized to optimize compatibility with a matrix; secondly, through copolymerization of monomers such as 2-sulfonic acid ethyl methacrylate, polyethylene glycol methacrylate and dimethylacryloyloxyphosphonic acid, the polarity and flexibility of the compatilizer are adjusted, and the interface bonding strength of the compatilizer to a CPVC matrix and a modified elastomer is improved, so that the mechanical property of the composite material is remarkably improved; finally, nano SiO2 is subjected to surface modification through a silane coupling agent, so that the dispersity of the inorganic filler and the binding force with a matrix are improved, and the rigidity and the thermal stability of the composite material are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of CPVC pipe preparation, and relates to a high-strength toughened CPVC pipe and a preparation method thereof. Background Art

[0002] Chlorinated polyvinyl chloride (CPVC) is a modified polyvinyl chloride (PVC) material obtained by chlorination treatment. It has high heat resistance, corrosion resistance and excellent electrical insulation, so it is widely used in pipelines, cables, electrical equipment and building materials. In the pipeline industry, CPVC pipes have been widely used in water supply and drainage, fire protection, industrial transportation and other fields due to their high temperature resistance, corrosion resistance, good mechanical properties and long service life. Especially in hot water pipes and industrial chemical transportation pipeline systems, CPVC pipes have become one of the important pipeline materials because they can withstand high temperatures and chemical corrosion. However, although CPVC pipes have excellent high temperature resistance and corrosion resistance, their brittleness and poor low temperature performance still exist, which is particularly obvious in low temperature environments or when subjected to external force impact. In the long-term use of CPVC pipes, due to the brittleness of the material itself and the effect of external impact, they are often prone to cracking or breaking, which is difficult to meet actual needs. Therefore, it is of great practical significance to develop a new type of high-strength toughened CPVC pipe. Summary of the invention

[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a high-strength toughened CPVC pipe and a preparation method thereof. A modified elastomer is prepared by an emulsion polymerization method, and the flexibility, polarity and interface compatibility are adjusted by introducing different monomers. A compatibilizer with high polarity and flexibility is prepared using a functional monomer of 2-sulfonic acid ethyl methacrylate, so as to improve the interface bonding force between the modified elastomer and the CPVC matrix and reduce interface defects. The surface of nano-SiO2 is modified by a silane coupling agent, so as to enhance the dispersibility and interface interaction of inorganic fillers in the matrix, further improve the rigidity, heat resistance and dimensional stability of the material, thereby meeting the needs of actual production.

[0004] To achieve this object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing a high-strength toughened CPVC pipe, the preparation method comprising: Step S1, adding sodium dodecylbenzene sulfonate and sodium bicarbonate to deionized water, heating to a first temperature, then mixing butadiene and divinylbenzene, adding to deionized water and stirring evenly, adding an initiator under a nitrogen atmosphere, and fully reacting at the first temperature, cooling to room temperature after the reaction to obtain a core layer emulsion, adding methyl methacrylate and an emulsifier to the core layer emulsion, heating to a second temperature, adding ammonium persulfate to fully react, and obtaining an inner shell layer emulsion; Step S2, adding butyl methacrylate, acrylonitrile, an emulsifier and an initiator to the inner shell emulsion, heating to a second temperature and continuing the reaction to obtain an intermediate shell emulsion, adding acrylic acid, epoxy acrylate, ethyl methacrylate and an initiator to the intermediate shell emulsion, heating to a third temperature, fully reacting to obtain a polar outer shell emulsion, maintaining the third temperature, adding vinyl triethoxysilane and ethylene oxide to continue the reaction, cooling to room temperature after the reaction is completed, filtering and washing, and then vacuum drying at a fourth temperature to obtain a modified elastomer; Step A1, adding octadecyl dimethacrylate and styrene to toluene, mixing well, adding ethyl bromide-2-bromopropionate, cuprous chloride and bipyridine, heating to the fifth temperature under a nitrogen atmosphere for sufficient reaction, cooling to room temperature after the reaction, adding cold methanol to collect the precipitate and washing to obtain product A; Step A2, adding product A to methanol, adding 2-sulfonic acid ethyl methacrylate, polyethylene glycol methacrylate, dimethacryloyloxyphosphonic acid, ethyl bromide-2-bromopropionate, cuprous chloride and bipyridine, heating to the fifth temperature for sufficient reaction, cooling to room temperature after the reaction, adding cold ethanol to collect and wash the precipitate, and placing the precipitate at the fourth temperature for vacuum drying to obtain a compatibilizer; Step A3, adding a silane coupling agent to an ethanol solution and adjusting the pH to 4, adding nano-SiO2 after stirring evenly, heating to a second temperature under a water bath condition and continuing the reaction, centrifuging and washing after the reaction is completed, and placing under vacuum drying at a fourth temperature to obtain modified nano-SiO2; Step S3, adding CPVC, modified elastomer, compatibilizer, modified nano-SiO2, calcium zinc stabilizer, zinc stearate and antioxidant 1010 into a melt mixer, mixing evenly, using a customized mold with a self-exhaust device and a mold, a die and a core rod that are all electroplated and mirror-finished to further plasticize the material, and installing a high-level water tank in the shaping stage to eliminate bubbles in the vacuum shaping box to stabilize the vacuum, and the grooved sizing sleeve ensures uniform and sufficient cooling, and a layer of water film is formed between the extruded pipe and the sizing sleeve to cover the pipe to ensure uniform cooling of the pipe, and a four-claw traction machine is used to clamp the product at multiple points and traction at a uniform speed to obtain a high-strength toughened CPVC pipe.

[0005] Butadiene is a conjugated diene monomer. Through its double bond, butadiene can undergo free radical polymerization to form polybutadiene. After polymerization, butadiene forms a long, flexible carbon main chain whose single bond can rotate freely. The resulting polybutadiene material has a large degree of freedom of molecular chain movement and exhibits the elasticity of rubber. This flexibility enables the core layer to deform when subjected to external forces and absorb impact energy, thereby playing a toughening role. The flexible chain segments of polybutadiene give the core layer good elasticity, allowing it to return to its original shape after being subjected to external forces, thereby improving the impact resistance of the core layer. Divinylbenzene is a cross-linking monomer containing two vinyl groups. Both vinyl groups on the divinylbenzene molecule can participate in free radical polymerization to form cross-linking points, integrating the butadiene chain into a three-dimensional network structure. The cross-linked three-dimensional network significantly improves the shape retention ability and structural stability of the core layer. The linear chain segments of polybutadiene are prone to slippage or irreversible plastic deformation when subjected to external forces. However, when divinylbenzene is introduced into the cross-linking points, different polymer chains are entangled together and slippage is restricted. Due to the existence of cross-linking points, the molecular chains are no longer completely free, but are constrained by the three-dimensional network, which prevents the polymer from irreversibly flowing or deforming under high temperature or stress conditions, thereby improving the shape stability of the material. When external force acts on the core layer, the flexible butadiene matrix can absorb a large amount of energy and deform. This energy absorption mechanism effectively slows down the propagation rate of the cracks. The cross-linking structure of divinylbenzene limits the crack propagation to a local area, preventing it from propagating rapidly along the molecular chain direction, thereby improving the crack resistance of the core layer.

[0006] Methyl methacrylate is a typical rigid monomer, and its polymer polymethyl methacrylate has a high glass transition temperature and good mechanical strength. The molecular structure of methyl methacrylate contains a methacrylate group. The double bond in this group is highly active and can form polymethyl methacrylate through free radical polymerization. The main chain is a linear long chain composed of CC single bonds. Since each carbon atom in the main chain is connected to a large side group (such as methyl and methyl ester groups), the movement of the chain segment is restricted by steric hindrance, resulting in a high rigidity of the molecular chain and difficulty in bending. At the same time, the methyl group of polymethyl methacrylate is a polar group, and the carbonyl group has a high electronegativity, resulting in the oxygen atom on the carbonyl group carrying a partial negative charge, while the carbon atom carries a partial positive charge. The entire methyl group forms an electric dipole, which can attract the methyl groups on the adjacent molecular chains through dipole-dipole interactions. In polymethyl methacrylate, since the methyl groups are regularly arranged along the molecular chains, the dipole-dipole interactions between the molecular chains are widely and evenly distributed. This interaction enhances the attraction between the molecular chains and increases the packing density of the molecular chains. In addition to the polar interactions of the methyl groups, the non-polar parts of the polymethyl methacrylate molecular chains (such as the CC bonds on the main chain and the methyl-CH3 in the side chains) will interact with other molecular chains through van der Waals forces, further enhancing the binding force between the molecular chains, prompting the polymethyl methacrylate molecular chains to be tightly stacked in space, reducing the gaps between the molecular chains, and improving the density and stability of the material. Polymethyl methacrylate forms a rigid outer shell (inner shell) in the core-shell particles, which wraps and protects the flexible butadiene rubber core layer. The rigid polymethyl methacrylate layer can effectively disperse external forces and prevent the rubber core layer from being damaged by local concentrated stress. The high mechanical strength of the polymethyl methacrylate layer enables the inner shell layer to withstand mechanical stress from the outside of the matrix, preventing the particles from collapsing or breaking under external forces. In addition, polybutadiene is a material with high elasticity but easy to age. The double bonds in its molecules are easily attacked by factors such as oxygen, ozone, and ultraviolet rays in the environment, leading to oxidative degradation. Double bond oxidation may generate degradation products such as peroxides, aldehydes, and ketones, which significantly reduce the mechanical properties of the rubber core, and then lose elasticity or become brittle. Polymethyl methacrylate has excellent weather resistance and chemical stability. It is coated on the outside of the rubber core to form a barrier to prevent oxygen, ozone and other environmental factors from directly contacting the rubber core. The high density and low permeability of polymethyl methacrylate further enhance the protective effect on the rubber core layer, thereby extending the service life of the core-shell particles.

[0007] The molecular structure of butyl methacrylate contains a long butyl chain, which is a non-polar, flexible chain segment. After polymerization, the butyl chain gives the copolymer chain segment higher flexibility and freedom of molecular chain movement, which makes the material of the middle shell layer have certain elasticity and toughness. The flexible chain segment of butyl methacrylate improves the ductility and deformation capacity of the middle shell layer by reducing the rigidity of the chain segment. When subjected to external force impact, the middle shell layer can absorb a certain amount of energy, alleviate the direct impact of external force on the core layer and the matrix, improve the overall flexibility of the core-shell particles, and effectively prevent the particles from breaking due to brittleness in the composite material. Acrylonitrile is a polar monomer, containing a very important polar nitrile group. The nitrile group has a strong polarity, the nitrogen atom carries a partial negative charge, and the carbon atom carries a partial positive charge. This polarity enables the acrylonitrile polymer chain segment to interact strongly with other polar molecules (CPVC matrix), and may form a dipole-dipole interaction with the polar chlorine atoms in CPVC, thereby enhancing the interfacial bonding force between the core-shell particles and the matrix. CPVC is a polar polymer. The increase in the degree of chlorination in the matrix significantly enhances the polarity of its molecular chain. The acrylonitrile segment introduced in the intermediate shell layer, through the high polarity of the nitrile group, has a stronger interfacial interaction with the polar segment of the CPVC matrix, thereby improving the dispersion and compatibility of the core-shell particles in the matrix, reducing the stress concentration at the interface between the two phases, and avoiding the interface peeling or crack propagation of the material. The flexible chain segments provided by butyl methacrylate can absorb part of the impact energy, while the polar nitrile groups introduced by acrylonitrile ensure the strong interface bonding between the intermediate shell layer and the polar matrix. In the composite material, when external force is applied to the core-shell particles, the intermediate shell layer can absorb energy through the deformation of the flexible chain segments and disperse stress through the interface bonding between the polar chain segments and the matrix.

[0008] The molecular structure of acrylic acid contains an unsaturated double bond and a carboxyl group. During polymerization, the double bond participates in free radical polymerization to form a polymer chain, while the carboxyl group remains on the side chain as a polar group. The carboxyl group is a strong polar group that can generate attraction with the polar chlorine atoms in the CPVC matrix through hydrogen bonds or dipole-dipole interactions. The carboxyl group can also serve as a chemical reaction site to react chemically with the subsequently introduced silane coupling agent or the hydroxyl group on the surface of nano-SiO2 to form a stable chemical bond. Epoxy acrylate contains a double bond and an epoxy group. The double bond is embedded in the polymer main chain through free radical polymerization, while the epoxy group is retained on the side chain as an active functional group. The epoxy group can react weakly with the polar chlorine atoms or residual trace hydroxyl groups in the CPVC matrix to form a bond. The epoxy group can react with the subsequently introduced silane coupling agent or the hydroxyl group on the surface of nano-SiO2 to form a chemical cross-linking network, which enhances the chemical bonding force between the outer shell layer and the matrix or filler. Ethyl methacrylate contains a double bond and an ethyl ester group. The polymer segment formed after polymerization has a high glass transition temperature, showing good hardness and heat resistance. The rigid main chain structure of ethyl methacrylate enhances the hardness and strength of the outer shell layer. The polar ester group interacts with the polar chlorine atoms in the CPVC matrix, further improving the interface bonding and avoiding particle agglomeration.

[0009] Octadecanyl dimethacrylate contains a double bond and a long-chain alkyl side chain. The long-chain alkyl is a non-polar and flexible chemical group with a large degree of freedom of movement of the molecular chain segment. Under the action of external force, this flexible chain segment can absorb and dissipate energy through deformation, thereby improving the toughness of the material. The molecular structure of styrene contains a benzene ring, which is a rigid group that limits the rotational freedom of the chain segment and improves the rigidity of the polymer chain. The polymer chain segment of styrene provides high tensile strength and shear resistance, making the material not only flexible but also strong. The hydrophobic part of styrene and the polar characteristics of the benzene ring can have a weak dipole-dipole interaction with the chlorine atoms in the CPVC matrix, enhancing the interfacial bonding force. On the basis of product A, 2-sulfonic acid ethyl methacrylate is introduced. The sulfonic acid group in the 2-sulfonic acid ethyl methacrylate molecule has strong polarity and can undergo strong dipole-dipole interaction with polar chlorine atoms in the CPVC matrix to enhance compatibility. The sulfonic acid group can also interact with other polar components through hydrogen bonds or electrostatic effects, further improving the interfacial adhesion of the material, preventing particle aggregation, and improving the uniformity and processing properties of the composite material. The polyethylene glycol methacrylate molecule contains long-chain polyoxyethylene groups, which exhibit high flexibility and good freedom of molecular chain segment movement, can absorb and dissipate external impact energy, and further enhance the toughening effect of the material. The phosphonic acid group in dimethylacryloxyphosphonic acid has high chemical reactivity and can undergo chemical reaction with the hydroxyl group on the surface of the inorganic filler (modified nano-SiO2) to form a stable chemical bond, thereby improving the interfacial bonding force between the compatibilizer and the inorganic filler.

[0010] Through the modification of silane coupling agent, epoxy functional groups are introduced into the surface of nano-SiO2, which can react chemically with polar or cross-linking sites in CPVC matrix to enhance the interfacial bonding force. At the same time, the functional groups can also chemically bond with other additives (such as compatibilizers, modified elastomer agents) to enhance the interface uniformity and stability of the composite material. The surface of the modified nano-SiO2 changes from a single polar hydroxyl group to an organic-inorganic composite surface, which reduces the surface energy between particles, reduces agglomeration, and improves its dispersion in the matrix. Nano-SiO2 is a high-strength, high-hardness inorganic material that can improve the rigidity and tensile strength of the composite material. The modification makes it evenly dispersed in the matrix, avoids stress concentration, and further enhances the mechanical properties of the composite material.

[0011] As a preferred technical solution of the present invention, in step S1, the mass of the sodium dodecylbenzene sulfonate is 2-3% of the mass of butadiene, for example, it can be 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0012] In some optional examples, the mass of the sodium bicarbonate is 0.5-1% of the mass of butadiene, for example, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0013] In some optional examples, the mass ratio of the deionized water to butadiene is 5:1.

[0014] In some optional instances, the first temperature is 60-70°C, for example, it can be 60.0°C, 61.0°C, 62.0°C, 63.0°C, 64.0°C, 65.0°C, 66.0°C, 67.0°C, 68.0°C, 69.0°C or 70.0°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] In some optional examples, the mass of divinylbenzene is 1.5-2% of the mass of butadiene, for example, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0016] In some optional examples, the initiator is potassium persulfate, and the mass of the initiator is 0.1-0.2% of the mass of butadiene, for example, it can be 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19% or 0.20%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] In some optional examples, the reaction time at the first temperature is 6-7h, for example, it can be 6.0h, 6.1h, 6.2h, 6.3h, 6.4h, 6.5h, 6.6h, 6.7h, 6.8h, 6.9h or 7.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] In some optional examples, the mass of the methyl methacrylate is 25-30% of the mass of butadiene, for example, 25.0%, 25.5%, 26.0%, 26.5%, 27.0%, 27.5%, 28.0%, 28.5%, 29.0%, 29.5%, or 30.0%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] In some optional examples, the mass of the emulsifier is 1-2% of the mass of butadiene, for example, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] In some optional instances, the second temperature is 70-80°C, for example, it can be 70.0°C, 71.0°C, 72.0°C, 73.0°C, 74.0°C, 75.0°C, 76.0°C, 77.0°C, 78.0°C, 79.0°C or 80.0°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] In some optional examples, the mass of the ammonium persulfate is 0.5-1% of the mass of butadiene, for example, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] In some optional examples, the reaction time after adding ammonium persulfate is 4-5h, for example, it can be 4.0h, 4.1h, 4.2h, 4.3h, 4.4h, 4.5h, 4.6h, 4.7h, 4.8h, 4.9h or 5.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] As a preferred technical solution of the present invention, in step S2, the mass of the butyl methacrylate is 15-20% of the mass of butadiene, for example, it can be 15.0%, 15.5%, 16.0%, 16.5%, 17.0%, 17.5%, 18.0%, 18.5%, 19.0%, 19.5% or 20.0%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] In some optional examples, the mass of the acrylonitrile is 8-10% of the mass of butadiene, for example, it can be 8.0%, 8.2%, 8.4%, 8.6%, 8.8%, 9.0%, 9.2%, 9.4%, 9.6%, 9.8% or 10.0%, but it is not limited to the listed values, and other unlisted values ​​in this numerical range are equally applicable. In some optional examples, the emulsifier is Tween-20, and the mass of the emulsifier is 1-2% of the mass of butadiene, for example, it can be 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2.0%, but it is not limited to the listed values, and other unlisted values ​​in this numerical range are equally applicable.

[0025] In some optional examples, the mass of the initiator added to the inner shell emulsion is 0.1-0.2% of the mass of butadiene, for example, it can be 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19% or 0.20%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] In some optional examples, the reaction time at the second temperature is 4-5h, for example, 4.0h, 4.1h, 4.2h, 4.3h, 4.4h, 4.5h, 4.6h, 4.7h, 4.8h, 4.9% or 5.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] In some optional examples, the mass of the acrylic acid is 8-10% of the mass of butadiene, for example, 8.0%, 8.2%, 8.4%, 8.6%, 8.8%, 9.0%, 9.2%, 9.4%, 9.6%, 9.8% or 10.0%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] In some optional examples, the mass of the epoxy acrylate is 8-10% of the mass of butadiene, for example, 8.0%, 8.2%, 8.4%, 8.6%, 8.8%, 9.0%, 9.2%, 9.4%, 9.6%, 9.8% or 10.0%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] In some optional examples, the mass of the ethyl methacrylate is 8-10% of the mass of butadiene, for example, 8.0%, 8.2%, 8.4%, 8.6%, 8.8%, 9.0%, 9.2%, 9.4%, 9.6%, 9.8% or 10.0%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] In some optional examples, the mass of the initiator added to the middle shell emulsion is 0.1-0.2% of the mass of butadiene, for example, it can be 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19% or 0.20%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] In some optional instances, the third temperature is 80-90°C, for example, it can be 80.0°C, 81.0°C, 82.0°C, 83.0°C, 84.0°C, 85.0°C, 86.0°C, 87.0°C, 88.0°C, 89.0°C or 90.0°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] In some optional examples, the reaction time after adding ethyl methacrylate is 6-7h, for example, it can be 6.0h, 6.1h, 6.2h, 6.3h, 6.4h, 6.5h, 6.6h, 6.7h, 6.8h, 6.9h or 7.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] In some optional examples, the mass of the vinyltriethoxysilane is 2-3% of the mass of butadiene, for example, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9% or 3.0%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] In some optional examples, the mass of the ethylene oxide is 2-3% of the mass of butadiene, for example, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9% or 3.0%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] In some optional examples, the reaction time after adding ethylene oxide is 2-3h, for example, it can be 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] In some optional instances, the fourth temperature is 50-60°C, for example, it can be 50.0°C, 51.0°C, 52.0°C, 53.0°C, 54.0°C, 55.0°C, 56.0°C, 57.0°C, 58.0°C, 59.0°C or 60.0°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] In some optional examples, the vacuum drying time is 10-12 h, for example, it can be 10.0 h, 10.2 h, 10.4 h, 10.6 h, 10.8 h, 11.0 h, 11.2 h, 11.4 h, 11.6 h, 11.8 h or 12.0 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] As a preferred technical solution of the present invention, in step A1, the mass ratio of octadecyl dimethacrylate to styrene is 3:2.

[0039] In some optional examples, the mass ratio of toluene to styrene is 10:1.

[0040] In some optional examples, the mass of the brominated ethyl-2-bromopropionate is 1-2% of the total mass of octadecyl dimethacrylate and styrene, for example, it can be 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2.0%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] In some optional examples, the mass of the cuprous chloride is 0.5-1% of the total mass of octadecyl dimethacrylate and styrene, for example, it can be 0.50%, 0.55%, 0.60%, 0.65%, 0.70%, 0.75%, 0.80%, 0.85%, 0.90%, 0.95% or 1.00%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] In some optional examples, the mass of the bipyridine is 1-2% of the total mass of octadecyl dimethacrylate and styrene, for example, it can be 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2.0%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] In some optional instances, the fifth temperature is 90-100°C, for example, it can be 90.0°C, 91.0°C, 92.0°C, 93.0°C, 94.0°C, 95.0°C, 96.0°C, 97.0°C, 98.0°C, 99.0°C or 100.0°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] In some optional examples, the reaction time at the fifth temperature is 6-7h, for example, it can be 6.0h, 6.1h, 6.2h, 6.3h, 6.4h, 6.5h, 6.6h, 6.7h, 6.8h, 6.9h or 7.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] As a preferred technical solution of the present invention, in step A2, the mass ratio of the product A to methanol is 1:4.

[0046] In some optional examples, the mass of the 2-sulfonic acid ethyl methacrylate is 20-30% of the mass of the product A, for example, it can be 20.0%, 21.0%, 22.0%, 23.0%, 24.0%, 25.0%, 26.0%, 27.0%, 28.0%, 29.0% or 30.0%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] In some optional examples, the mass ratio of 2-sulfonic acid ethyl methacrylate, polyethylene glycol methacrylate, and dimethacryloyloxyphosphonic acid is 2:2:1.

[0048] In some optional examples, the mass of the brominated ethyl-2-bromopropionate is 1-2% of the total mass of 2-sulfonic acid ethyl methacrylate, polyethylene glycol methacrylate, and dimethacryloyloxyphosphonic acid, for example, it can be 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2.0%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] In some optional examples, the mass of the cuprous chloride is 0.5-1% of the total mass of 2-sulfonic acid ethyl methacrylate, polyethylene glycol methacrylate, and dimethacryloyloxyphosphonic acid, for example, it can be 0.50%, 0.55%, 0.60%, 0.65%, 0.70%, 0.75%, 0.80%, 0.85%, 0.90%, 0.95% or 1.00%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] In some optional examples, the mass of the bipyridine is 1-2% of the total mass of 2-sulfonic acid ethyl methacrylate, polyethylene glycol methacrylate, and dimethacryloxyphosphonic acid, for example, it can be 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2.0%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] In some optional examples, the reaction time after adding bipyridine is 6-7h, for example, it can be 6.0h, 6.1h, 6.2h, 6.3h, 6.4h, 6.5h, 6.6h, 6.7h, 6.8h, 6.9h or 7.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] In some optional examples, the vacuum drying time is 10-12h, for example, it can be 10.0h, 10.2h, 10.4h, 10.6h, 10.8h, 11.0h, 11.2h, 11.4h, 11.6h, 11.8h or 12.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0053] As a preferred technical solution of the present invention, in step A3, the volume ratio of ethanol to deionized water in the ethanol solution is 40:1.

[0054] In some optional examples, the silane coupling agent is KH-550, and its mass is 2-3% of the mass of nano-SiO2, for example, it can be 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9% or 3.0%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] In some optional examples, the volume mass ratio of the ethanol solution to nano-SiO2 is 20mL:1g.

[0056] In some optional examples, the water bath heating reaction time is 2-3h, for example, it can be 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0057] In some optional examples, the vacuum drying time is 10-12h, for example, it can be 10.0h, 10.2h, 10.4h, 10.6h, 10.8h, 11.0h, 11.2h, 11.4h, 11.6h, 11.8h or 12.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] As a preferred technical solution of the present invention, in step S3, the antioxidant is antioxidant 1010, and the mass ratio of the CPVC, modified elastomer, compatibilizer, modified nano-SiO2, calcium zinc stabilizer, zinc stearate and antioxidant 1010 is 100: (10-15): (2-4): (2-5): (2-3): (1-2): (0.5-1).

[0059] In a second aspect, a high-strength toughened CPVC pipe obtained by the preparation method described in the first aspect is provided.

[0060] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) methyl methacrylate is polymerized to form polymethyl methacrylate, which has a high molecular chain rigidity and is not easy to bend. At the same time, it can attract the methyl ester groups on the adjacent molecular chains through dipole-dipole interaction, thereby enhancing the attraction between the molecular chains and improving the packing density of the molecular chains. In addition, polymethyl methacrylate wraps and protects the flexible butadiene rubber core layer. The rigid polymethyl methacrylate layer can effectively disperse external forces and forms a barrier to enhance the protection of the rubber core layer, thereby extending the service life of the modified elastomer. (2) The nitrile group is introduced into the modified elastomer, so that the acrylonitrile polymer chain segment can interact strongly with the polar molecule CPVC, thereby enhancing the interface bonding force between the core-shell particles and the matrix and improving the dispersibility of the modified elastomer. and compatibility, which can reduce stress concentration at the interface of the two phases and avoid interface peeling or crack propagation of the material; (3) 2-sulfonic acid ethyl methacrylate is introduced into the compatibilizer. The sulfonic acid group in the 2-sulfonic acid ethyl methacrylate molecule has a strong polarity and can have a strong dipole-dipole interaction with the polar chlorine atoms in the CPVC matrix to enhance compatibility. The sulfonic acid group can also interact with other polar components through hydrogen bonds or electrostatic effects, further improving the interfacial adhesion of the material and preventing particle aggregation; (4) The phosphonic acid group in dimethylacryloxyphosphonic acid introduced into the compatibilizer has a high chemical reactivity and can react chemically with the hydroxyl groups on the surface of the modified nano-SiO2 to form a stable chemical bond, thereby improving the interfacial bonding strength between the compatibilizer and the inorganic filler. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 This is a TEM image of the modified elastomer prepared in Example 1 of the present invention; Figure 2 This is a SEM image of the compatibilizer prepared in Example 1 of the present invention; Figure 3 This is the SEM image of the modified SiO2 prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0062] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.

[0063] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products without any further purification treatment.

[0064] Example 1

[0065] This embodiment provides a method for preparing a high-strength toughened CPVC pipe, and the preparation method specifically comprises the following steps: Step S1, adding 1g of sodium dodecylbenzene sulfonate and 0.25g of sodium bicarbonate to 250g of deionized water, heating to 63°C, then mixing 50g of butadiene and 0.75g of divinylbenzene, adding to deionized water and stirring evenly, adding 0.05g of potassium persulfate under nitrogen atmosphere, and fully reacting at 63°C for 6.2h, cooling to room temperature after the reaction to obtain a core layer emulsion, adding 12.5g of methyl methacrylate and 0.5g of Tween-20 to the core layer emulsion, heating to 77°C, adding 0.25g of ammonium persulfate and fully reacting for 4.3h to obtain an inner shell layer emulsion; Step S2, adding 10g butyl methacrylate, 4g acrylonitrile, 0.5g Tween-20 and 0.06g potassium persulfate to the inner shell emulsion, heating to 73°C and continuing to react for 4.6h to obtain an intermediate shell emulsion, adding 4.5g acrylic acid, 5g epoxy acrylate, 4g ethyl methacrylate and 0.07g potassium persulfate to the intermediate shell emulsion, heating to 87°C, fully reacting for 6.4h to obtain a polar outer shell emulsion, maintaining 87°C, adding vinyl triethoxysilane and ethylene oxide to continue to react for 2.8h, cooling to room temperature after the reaction is completed, filtering and washing, and then placing under vacuum at a fourth temperature of 55°C for 10.8h to obtain a modified elastomer; Step A1, add 30g of octadecyl dimethacrylate and 20g of styrene to 200g of toluene, mix well, add 0.5g of ethyl bromide-2-bromopropionate, 0.25g of cuprous chloride and 0.5g of bipyridine, heat to 96°C under a nitrogen atmosphere to react for 6.7h, cool to room temperature after the reaction, add cold methanol to collect the precipitate and wash to obtain product A; Step A2, add 10g of product A to 40g of methanol, add 2g of 2-sulfonic acid ethyl methacrylate, 2g of polyethylene glycol methacrylate, 1g of dimethyl acryloyloxyphosphonic acid, 0.05g of bromoethyl-2-bromopropionate, 0.05g of cuprous chloride and 0.05g of bipyridine, heat to 98°C and react for 6.7h, cool to room temperature after the reaction, add cold ethanol to collect and wash the precipitate, and place the precipitate at 55°C under vacuum and dry for 11h to obtain a compatibilizer; Step A3, adding 0.3 g of silane coupling agent to 200 mL of ethanol solution and adjusting the pH to 4, stirring evenly, adding 10 g of nano-SiO2, heating to 77° C. in a water bath and continuing the reaction for 2.6 h, centrifuging and washing after the reaction, and placing under vacuum drying at 54° C. for 10.6 h to obtain modified nano-SiO2; Step S3, adding 100g CPVC, 12g modified elastomer, 2.0g compatibilizer, 2g modified nano-SiO2, 2.3g calcium zinc stabilizer, 1.6g zinc stearate and 0.75g antioxidant 1010 into a melt mixer, mixing evenly, using a customized mold with a self-exhaust device and a mold, a die and a mandrel that are all mirror-plated to further plasticize the material, and in the shaping stage, installing a high-level water tank to remove bubbles in the vacuum shaping box to stabilize the vacuum, and the grooved sizing sleeve ensures uniform and sufficient cooling, and a layer of water film is formed between the extruded pipe and the sizing sleeve to cover the pipe to ensure uniform cooling of the pipe, and a four-claw traction machine is used to clamp the product at multiple points and traction at a uniform speed to obtain a high-strength toughened CPVC pipe.

[0066] Figure 1 This is the TEM image of the modified elastomer prepared in this example. Figure 2 This is the SEM image of the compatibilizer prepared in Example. Figure 3 This is the SEM image of the modified SiO2 prepared in the example.

[0067] Example 2

[0068] This embodiment provides a method for preparing a high-strength toughened CPVC pipe, and the preparation method specifically comprises the following steps: Step S1, adding 1.2g of sodium dodecylbenzene sulfonate and 0.4g of sodium bicarbonate to 200g of deionized water, heating to 60°C, then mixing 40g of butadiene and 0.8g of divinylbenzene, adding to the deionized water and stirring evenly, adding 0.08g of potassium persulfate under a nitrogen atmosphere, and fully reacting at 60°C for 7.0h, cooling to room temperature after the reaction to obtain a core layer emulsion, adding 12g of methyl methacrylate and 0.8g of Tween-20 to the core layer emulsion, heating to 70°C, adding 0.4g of ammonium persulfate and fully reacting for 4.0h to obtain an inner shell layer emulsion; Step S2, adding 6g of butyl methacrylate, 3.6g of acrylonitrile, 0.8g of Tween-20, and 0.05g of potassium persulfate to the inner shell emulsion, heating to 70°C and continuing to react for 4.0h to obtain an intermediate shell emulsion, adding 4g of acrylic acid, 3.2g of epoxy acrylate, 3.6g of ethyl methacrylate and 0.06g of potassium persulfate to the intermediate shell emulsion, heating to 90°C, fully reacting for 6.8h to obtain a polar outer shell emulsion, maintaining 90°C, adding vinyl triethoxysilane and ethylene oxide to continue to react for 3.0h, cooling to room temperature after the reaction is completed, filtering and washing, and then placing under vacuum at a fourth temperature of 50°C for 10.0h to obtain a modified elastomer; Step A1, add 27g of octadecyl dimethacrylate and 18g of styrene to 180g of toluene, mix well, add 0.9g of ethyl bromide-2-bromopropionate, 0.45g of cuprous chloride and 0.9g of bipyridine, heat to 100°C under a nitrogen atmosphere to react for 6.0h, cool to room temperature after the reaction, add cold methanol to collect the precipitate and wash to obtain product A; Step A2, add 15g of product A to 60g of methanol, add 3g of 2-sulfonic acid ethyl methacrylate, 3g of polyethylene glycol methacrylate, 1.5g of dimethyl acryloyloxyphosphonic acid, 0.15g of bromoethyl-2-bromopropionate, 0.07g of cuprous chloride and 0.15g of bipyridine, heat to 100°C and react for 6.0h, cool to room temperature after the reaction, add cold ethanol to collect and wash the precipitate, and place the precipitate at 50°C and vacuum dry for 10.5h to obtain a compatibilizer; Step A3, adding 0.24g of silane coupling agent to 240mL of ethanol solution and adjusting the pH to 4, stirring evenly and adding 12g of nano-SiO2, heating to 80°C in a water bath and continuing the reaction for 2.0h, centrifugally washing after the reaction and placing it at 50°C for vacuum drying for 12.0h to obtain modified nano-SiO2; Step S3, adding 100g CPVC, 10g modified elastomer, 2.6g compatibilizer, 3g modified nano-SiO2, 2.0g calcium zinc stabilizer, 1.0g zinc stearate and 0.5g antioxidant 1010 into a melt mixer, mixing evenly, using a customized mold with a self-exhaust device and a mold, a die and a mandrel that are all electroplated and mirror-finished to further plasticize the material, and in the shaping stage, installing a high-level water tank to remove bubbles in the vacuum shaping box to stabilize the vacuum, and the grooved sizing sleeve ensures uniform and sufficient cooling, and a layer of water film is formed between the extruded pipe and the sizing sleeve to cover the pipe to ensure uniform cooling of the pipe, and a four-claw traction machine is used to clamp the product at multiple points and traction at a uniform speed to obtain a high-strength toughened CPVC pipe.

[0069] Example 3

[0070] This embodiment provides a method for preparing a high-strength toughened CPVC pipe, and the preparation method specifically comprises the following steps: Step S1, adding 1.5g of sodium dodecylbenzene sulfonate and 0.3g of sodium bicarbonate to 300g of deionized water, heating to 67°C, then mixing 60g of butadiene and 0.9g of divinylbenzene, adding to deionized water and stirring evenly, adding 0.09g of potassium persulfate under nitrogen atmosphere, and fully reacting at 67°C for 6.4h, cooling to room temperature after the reaction to obtain a core layer emulsion, adding 16.8g of methyl methacrylate and 0.9g of Tween-20 to the core layer emulsion, heating to 74°C, adding 0.3g of ammonium persulfate and fully reacting for 4.7h to obtain an inner shell layer emulsion; Step S2, adding 12g butyl methacrylate, 4.8g acrylonitrile, 0.9g Tween-20 and 0.09g potassium persulfate to the inner shell emulsion, heating to 80°C and continuing to react for 4.3h to obtain an intermediate shell emulsion, adding 4.8g acrylic acid, 4.8g epoxy acrylate, 4.8g ethyl methacrylate and 0.1g potassium persulfate to the intermediate shell emulsion, heating to 84°C, fully reacting for 7.0h to obtain a polar outer shell emulsion, maintaining 84°C, adding vinyl triethoxysilane and ethylene oxide to continue to react for 2.0h, cooling to room temperature after the reaction is completed, filtering and washing, and then placing under vacuum at a fourth temperature of 60°C for 12.0h to obtain a modified elastomer; Step A1, add 33g of octadecyl dimethacrylate and 22g of styrene to 220g of toluene, mix well, add 0.55g of ethyl bromide-2-bromopropionate, 0.44g of cuprous chloride and 0.55g of bipyridine, heat to 93°C under a nitrogen atmosphere to react for 6.3h, cool to room temperature after the reaction, add cold methanol to collect the precipitate and wash to obtain product A; Step A2, add 12g of product A to 48g of methanol, add 2.4g of 2-sulfonic acid ethyl methacrylate, 2.4g of polyethylene glycol methacrylate, 1.2g of dimethyl acryloyloxyphosphonic acid, 0.12g of brominated ethyl-2-bromopropionate, 0.06g of cuprous chloride and 0.12g of bipyridine, heat to 94°C and react for 6.4h, cool to room temperature after the reaction, add cold ethanol to collect and wash the precipitate, and place the precipitate at 60°C under vacuum and dry for 12.0h to obtain a compatibilizer; Step A3, adding 0.3 g of silane coupling agent to 300 mL of ethanol solution and adjusting the pH to 4, stirring evenly and adding 15 g of nano-SiO2, heating to 76°C in a water bath and continuing the reaction for 2.4 h, centrifuging and washing after the reaction and placing under vacuum drying at 57°C for 11.5 h to obtain modified nano-SiO2; Step S3, adding 100g CPVC, 15g modified elastomer, 3.4g compatibilizer, 4g modified nano-SiO2, 2.7g calcium zinc stabilizer, 1.4g zinc stearate and 0.84g antioxidant 1010 into a melt mixer, mixing evenly, using a customized mold with a self-exhaust device and a mold, a die and a mandrel that are all mirror-plated to further plasticize the material, and in the shaping stage, installing a high-level water tank to remove bubbles in the vacuum shaping box to stabilize the vacuum, and the grooved sizing sleeve ensures uniform and sufficient cooling, and a layer of water film is formed between the extruded pipe and the sizing sleeve to cover the pipe to ensure uniform cooling of the pipe, and a four-claw traction machine is used to clamp the product at multiple points and traction at a uniform speed to obtain a high-strength toughened CPVC pipe.

[0071] Example 4

[0072] This embodiment provides a method for preparing a high-strength toughened CPVC pipe, and the preparation method specifically comprises the following steps: Step S1, adding 1.3g of sodium dodecylbenzene sulfonate and 0.38g of sodium bicarbonate to 250g of deionized water, heating to 70°C, then mixing 50g of butadiene and 1g of divinylbenzene, adding to the deionized water and stirring evenly, adding 0.1g of potassium persulfate under a nitrogen atmosphere, and fully reacting at 70°C for 6.0h, cooling to room temperature after the reaction to obtain a core layer emulsion, adding 15g of methyl methacrylate and 0.1g of Tween-20 to the core layer emulsion, heating to 80°C, adding 0.38g of ammonium persulfate and fully reacting for 5.0h to obtain an inner shell layer emulsion; Step S2, adding 7.5g butyl methacrylate, 5g acrylonitrile, 0.1g Tween-20 and 0.08g potassium persulfate to the inner shell emulsion, heating to 77°C and continuing to react for 5.0h to obtain an intermediate shell emulsion, adding 5g acrylic acid, 5g epoxy acrylate, 5g ethyl methacrylate and 0.06g potassium persulfate to the intermediate shell emulsion, heating to 80°C, fully reacting for 6.0h to obtain a polar outer shell emulsion, maintaining 80°C, adding vinyl triethoxysilane and ethylene oxide to continue to react for 2.7h, cooling to room temperature after the reaction is completed, filtering and washing, and then placing under vacuum at a fourth temperature of 52°C for 11.4h to obtain a modified elastomer; Step A1, add 36g of octadecyl dimethacrylate and 24g of styrene to 240g of toluene, mix well, add 1.2g of ethyl bromide-2-bromopropionate, 0.6g of cuprous chloride and 1.2g of bipyridine, heat to 90°C under a nitrogen atmosphere and react for 7.0h. After the reaction is completed, cool to room temperature, add cold methanol to collect the precipitate and wash to obtain product A; Step A2, add 14g of product A to 56g of methanol, add 2.8g of 2-sulfonic acid ethyl methacrylate, 2.8g of polyethylene glycol methacrylate, 1.4g of dimethyl acryloyloxyphosphonic acid, 0.07g of brominated ethyl-2-bromopropionate, 0.07g of cuprous chloride and 0.07g of bipyridine, heat to 90°C and react for 7.0h, cool to room temperature after the reaction, add cold ethanol to collect and wash the precipitate, and place the precipitate at 57°C under vacuum and dry for 11.3h to obtain a compatibilizer; Step A3, adding 0.42g of silane coupling agent to 280mL of ethanol solution and adjusting the pH to 4, stirring evenly and adding 14g of nano-SiO2, heating to 70°C in a water bath and continuing the reaction for 3.0h, centrifugally washing after the reaction and placing at 60°C for vacuum drying for 10.0h to obtain modified nano-SiO2; Step S3, adding 100g CPVC, 13g modified elastomer, 4.0g compatibilizer, 5g modified nano-SiO2, 3.0g calcium zinc stabilizer, 2.0g zinc stearate and 1.0g antioxidant 1010 into a melt mixer, mixing evenly, using a customized mold with a self-exhaust device and a mold, a die and a mandrel that are all mirror-plated to further plasticize the material, and in the shaping stage, installing a high-level water tank to remove bubbles in the vacuum shaping box to stabilize the vacuum, and the grooved sizing sleeve ensures uniform and sufficient cooling, and a layer of water film is formed between the extruded pipe and the sizing sleeve to cover the pipe to ensure uniform cooling of the pipe, and a four-claw traction machine is used to clamp the product at multiple points and traction at a uniform speed to obtain a high-strength toughened CPVC pipe.

[0073] Comparative Example 1 This comparative example provides a method for preparing a high-strength toughened CPVC pipe, which differs from the embodiment in that the mass of butyl methacrylate in step S2 is 20 g, which is 10 g more than that in embodiment 1, and the other process parameters and operating conditions are exactly the same as those in embodiment 1.

[0074] Comparative Example 2 This comparative example provides a method for preparing a high-strength toughened CPVC pipe, which differs from the embodiment in that the mass of butyl methacrylate in step S2 is 2 g, which is 8 g less than that in embodiment 1, and the other process parameters and operating conditions are exactly the same as those in embodiment 1.

[0075] Comparative Example 3 This comparative example provides a method for preparing a high-strength toughened CPVC pipe, which differs from the example in that the mass of 2-sulfonic acid ethyl methacrylate in step A2 is 4 g, and the mass of butyl methacrylate is increased by 2 g compared with Example 1, and the other process parameters and operating conditions are exactly the same as those in Example 1.

[0076] Comparative Example 4 This comparative example provides a method for preparing a high-strength toughened CPVC pipe, which differs from the example in that the mass of 2-sulfonic acid ethyl methacrylate in step A2 is 0.5 g, and the mass of butyl methacrylate is reduced by 1.5 g compared with Example 1, and the other process parameters and operating conditions are exactly the same as those in Example 1.

[0077] The flattening test standard of the CPVC pipe prepared in the present invention is DL T 802.7-2010; the drop weight impact test standard is DL T 802.7-2010; the tensile strength test standard is GB / T 8804.3-2003; the elongation at break test standard is GB / T 8804.3-2003; the bending strength test standard is GB / T 8804.3-2003; and the Vicat softening temperature test standard is GB / T 1633-2000. The test results are shown in Table 1.

[0078] Table 1 Test results of high-strength toughened CPVC pipes prepared in Examples 1-4 and Comparative Examples 1-4

[0079] It can be seen from the data in Table 1 that, compared with Example 1, the results of the flattening test and the drop hammer impact test of Comparative Example 1 remain unchanged, the tensile strength decreases, the elongation at break increases, the bending strength decreases, and the Vicat softening temperature decreases; the flattening test and the drop hammer impact test of Comparative Example 2 show cracks, increased tensile strength, decreased elongation at break, increased bending strength, and increased Vicat softening temperature. This is because butyl methacrylate is a flexible monomer, and its long-chain butyl side groups provide a large intermolecular gap and freedom of segment movement, which can significantly reduce the glass transition temperature of the polymer, thereby enhancing the flexibility and impact resistance of the elastomer. In Comparative Example 1, there is too much butyl methacrylate, the flexible segments in the material increase, and the flexibility of the pipe increases, but the increase in the flexible segments weakens the strong interaction between the molecular chains, resulting in a decrease in the overall strength, and the Vicat softening temperature of the material decreases accordingly. In Comparative Example 2, there is too little butyl methacrylate, the toughness of the material decreases, and the CPVC pipe is more prone to cracks. The reduction of flexible monomers leads to enhanced rigidity of the shell, increased interaction between molecular chains, improved material strength, and reduced elongation at break. The reduction of flexible monomers leads to an increase in the glass transition temperature of the material, and the Vicat softening temperature increases accordingly.

[0080] Compared with Example 1, the flattening test and the drop hammer impact test of Comparative Example 3 showed cracks, increased tensile strength, decreased elongation at break, increased flexural strength, and increased Vicat softening temperature; the flattening test and the drop hammer impact test of Comparative Example 4 showed cracks, decreased tensile strength, increased elongation at break, decreased flexural strength, and decreased Vicat softening temperature. The sulfonic acid group in 2-sulfonic acid ethyl methacrylate has a strong polarity, and enhances the interfacial binding force with the chlorine atoms in CPVC through dipole-dipole interaction or hydrogen bond interaction. The sulfonic acid group enhances the entanglement degree of the molecular chain through the electrostatic interaction or hydrogen bond interaction between molecules, and the sulfonic acid group introduces a certain rigidity. In Comparative Example 3, too much 2-sulfonic acid ethyl methacrylate will introduce too strong polar interaction, reduce the flexibility of the material, enhance the rigidity and brittleness, increase the strength of the material, and reduce the elongation at break. The introduction of the sulfonic acid group enhances the interaction between the molecular chains and increases the Vicat softening temperature of the material. In Comparative Example 4, the amount of 2-sulfonic acid ethyl methacrylate is too little, the interface polarity is insufficient, the binding force between the CPVC matrix and the modified compatibilizer is weakened, resulting in an increase in the interface defects of the material and a weakening of the interaction between the molecular chains.

[0081] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a high-strength toughened CPVC pipe, characterized in that: The preparation method is: Step S1, adding sodium dodecylbenzene sulfonate and sodium bicarbonate into deionized water, then mixing butadiene and divinylbenzene and adding them into deionized water, adding an initiator under a nitrogen atmosphere, reacting to obtain a core layer emulsion, adding methyl methacrylate and an emulsifier into the core layer emulsion, and adding ammonium persulfate to fully react to obtain an inner shell layer emulsion; Step S2, adding butyl methacrylate, acrylonitrile, an emulsifier and an initiator to the inner shell emulsion to react to obtain an intermediate shell emulsion, adding acrylic acid, epoxy acrylate, ethyl methacrylate and an initiator to the intermediate shell emulsion to react to obtain a polar outer shell emulsion, adding vinyl triethoxysilane and ethylene oxide to continue the reaction to obtain a modified elastomer; Step S3, adding CPVC, modified elastomer, compatibilizer, modified nano-SiO2, calcium zinc stabilizer, zinc stearate and antioxidant into a melt mixer, and extruding to obtain a high-strength toughened CPVC pipe.

2. The method for preparing a high-strength toughened CPVC pipe according to claim 1, characterized in that: The preparation method of the compatibilizer comprises: Step A1, adding octadecyl dimethacrylate and styrene to toluene, and then adding ethyl bromide-2-bromopropionate, cuprous chloride and bipyridine, and heating to react under a nitrogen atmosphere to obtain product A; Step A2, adding product A to methanol, adding 2-sulfonic acid ethyl methacrylate, polyethylene glycol methacrylate, dimethylacryloyloxyphosphonic acid, brominated ethyl-2-bromopropionate, cuprous chloride and bipyridine, and heating to react to obtain a compatibilizer.

3. The method for preparing a high-strength toughened CPVC pipe according to claim 1, characterized in that: The preparation method of the modified nano-SiO2 comprises: Step A3, adding a silane coupling agent to an ethanol solution and adjusting the pH to 4, adding nano-SiO2, and heating the solution in a water bath to react to obtain modified nano-SiO2.

4. The method for preparing a high-strength toughened CPVC pipe according to claim 1, characterized in that: In step S1, The mass of the sodium dodecylbenzene sulfonate is 2-3% of the mass of butadiene; The mass of the sodium bicarbonate is 0.5-1% of the mass of butadiene; The mass of divinylbenzene is 1.5-2% of the mass of butadiene; The mass of the methyl methacrylate is 25-30% of the mass of butadiene.

5. The method for preparing a high-strength toughened CPVC pipe according to claim 1, characterized in that: In step S2, The mass of the butyl methacrylate is 15-20% of the mass of butadiene; The mass of acrylonitrile is 8-10% of the mass of butadiene; The mass of the initiator added to the inner shell emulsion is 0.1-0.2% of the mass of butadiene; The mass of the acrylic acid is 8-10% of the mass of butadiene; The mass of the epoxy acrylate is 8-10% of the mass of butadiene; The mass of the initiator added to the intermediate shell emulsion is 0.1-0.2% of the mass of butadiene; The mass of the vinyl triethoxysilane is 2-3% of the mass of butadiene; The mass of the ethylene oxide is 2-3% of the mass of butadiene.

6. The method for preparing a high-strength toughened CPVC pipe according to claim 1, characterized in that: In step S3, The mass ratio of the CPVC, modified elastomer, compatibilizer, modified nano-SiO2, calcium zinc stabilizer, zinc stearate and antioxidant is 100: (10-15): (2-4): (2-5): (2-3): (1-2): (0.5-1).

7. The method for preparing a high-strength toughened CPVC pipe according to claim 2, characterized in that: In step A1, The mass ratio of octadecyl dimethacrylate to styrene is 3:2; The mass of the brominated ethyl-2-bromopropionate is 1-2% of the total mass of octadecyl dimethacrylate and styrene; The mass of the cuprous chloride is 0.5-1% of the total mass of octadecyl dimethacrylate and styrene; The mass of the bipyridine is 1-2% of the total mass of octadecyl dimethacrylate and styrene.

8. The method for preparing a high-strength toughened CPVC pipe according to claim 2, characterized in that: In step A2, The mass of the 2-sulfonic acid ethyl methacrylate is 20-30% of the mass of the product A; The mass ratio of the 2-sulfonic acid ethyl methacrylate, polyethylene glycol methacrylate, and dimethacryloyloxyphosphonic acid is 2:2:1; The mass of the brominated ethyl-2-bromopropionate is 1-2% of the total mass of 2-sulfonic acid ethyl methacrylate, polyethylene glycol methacrylate, and dimethacryloyloxyphosphonic acid; The mass of the cuprous chloride is 0.5-1% of the total mass of 2-sulfonic acid ethyl methacrylate, polyethylene glycol methacrylate, and dimethacryloyloxyphosphonic acid; The mass of the bipyridine is 1-2% of the total mass of 2-sulfonic acid ethyl methacrylate, polyethylene glycol methacrylate and dimethacryloyloxyphosphonic acid.

9. The method for preparing a high-strength toughened CPVC pipe according to claim 3, characterized in that: In step A3, The silane coupling agent is KH-550, and its mass is 2-3% of the mass of nano-SiO2; The volume mass ratio of the ethanol solution to the nano-SiO2 is 20 mL:1 g.

10. A high-strength toughened CPVC pipe obtained according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Synthesis method for high impact PVC modifier

    CN104292399A

  • Nano silicon dioxide-PMMA-b-PS polymer material and preparation method thereof

    CN114685737A

  • Curable resin composition containing polymer particles

    TW201434940A

Cited By

  • High-temperature-resistant flame-retardant PVC (polyvinyl chloride) material and preparation method thereof

    CN120040887A

  • A high-temperature resistant and flame-retardant PVC material and its preparation method

    CN120040887B

  • High-toughness weather-resistant high-temperature-resistant chlorinated polyvinyl chloride and production method thereof

    CN120349469A